E-Learning Berbasis Mobile Pada SMK Negeri 1 Muaro Jambi - Safitri, Feny; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2022)
Since the introduction of online schools at SMK Negeri 1 Muaro Jambi due to the covid-19 pandemic, usually face-to-face learning has turned online. The online learning method at SMK Negeri 1 Muaro Jambi currently uses whatsapp application, but the features that can be utilized are few and less effective if used for the long term. For example, when students send assignments via photos sent via WhatsApp it often makes the storage on the smartphone full. Therefore, with mobile-based e-learning is expected to be a learning medium that can support the learning process online. The purpose of this research is to analyze and design a mobile-based e-learning system at SMK Negeri 1 Muaro Jambi. The system modeling tools used are UML (Unified Modeling Language) and Adobe XD to design prototypes. Suggestions for further research are expected to design an overall system that contains a notification menu.